2020
DOI: 10.1021/acs.jafc.9b07446
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Catalytic Synthesis of Gemini Lipoamino Acids Based on Multiple Hydrogen-Bonding Interactions in Natural Deep Eutectic Solvents-Enzyme System

Abstract: In the previous studies, gemini lipoamino acids (GLAA) were always synthesized by complex multistep organic synthesis, which involved a large number of byproducts and organic solvents. To develop a straightforward, efficient, and renewable synthesis strategy for GLAA, in this study, a type of novel green solvents, natural deep eutectic solvents (NADESs), were adopted as the solvents for these reactions. Five commercial enzymes were involved in the enzyme screening section, and Candida antarctica lipase B (CALB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Coincidentally, D-xylose laurate esters and L-arabinose laurate esters can be obtained via the esterification of sugars and vinyl laurate in 2-methyl-2-butanol with the catalysis of Novozyme 435 [52]. The lipase-catalyzed acylation reaction has also been widely investigated recently, and it has been found that CALB has a higher efficiency than D-Aminoacylase from Escherichia coli, and lipase from porcine pancreas, et al in the acylation of fatty acids and amino acids [1,53,54].…”
Section: Lipases As a Powerful Catalyst In The Food Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Coincidentally, D-xylose laurate esters and L-arabinose laurate esters can be obtained via the esterification of sugars and vinyl laurate in 2-methyl-2-butanol with the catalysis of Novozyme 435 [52]. The lipase-catalyzed acylation reaction has also been widely investigated recently, and it has been found that CALB has a higher efficiency than D-Aminoacylase from Escherichia coli, and lipase from porcine pancreas, et al in the acylation of fatty acids and amino acids [1,53,54].…”
Section: Lipases As a Powerful Catalyst In The Food Fieldmentioning
confidence: 99%
“…With the deepening of investigations, researchers have also found that the catalytic efficiency of lipases, especially in the esterification reaction and acylation reaction, is significantly affected by the solvent [1,[55][56][57]. Most recently, some novel green solvents were found to have great advantages in terms of the dissolution substrate and low-cost preparation, and are easy to separate and purify in enzymatic reactions.…”
Section: Lipases As a Powerful Catalyst In The Food Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep eutectic solvents (DESs), which can be prepared by blending a hydrogen-bond-acceptor (e.g., choline chloride) and a hydrogen-bond-donor (e.g., amines, carboxylic acids, and polyols) [41][42][43], are recognized as green solvents. They have been extensively utilized as a chemical or biochemical reaction medium for enhancing catalytic efficiency [44][45][46][47]. Some DESs have been applied as a tool for biocatalysis, either as solvents or as separative agents to overcome challenging workup procedures [48][49][50].…”
Section: Introductionmentioning
confidence: 99%